Exploring the Presence of Beauty Cage in Accounting Education: Evidence from Indonesia - ARI KAMAYANTI; IWAN TRIYUWONO; GUGUS IRIANTOAJI; DEDI MULAWARMAN (The Indonesian Journal of Accounting Research, 2013)
Accounting education is presently trapped into reaching concepts of “beauty”. These represent masculinity and colonization. Currently, accounting education is regarded beautiful if it uses a masculine approach that relies greatly on rationalism and if it is used to control and maintain status quo through colonization. Paulo Freire’s dialogic education liberation, particularly coding as the first stage of reflection, namely Freirean Coding, is employed to define and explore the beauty cage. The article provides empirical evidence that such a cage exists in Indonesian accounting education. This research aims to awaken consciousness that accounting education must embark upon a change to liberate itself from the beauty cage.